Karakteristik Mekanis Dari Campuran Abu Terbang Dan Abu Dasar Dalam Geoteknik - Ridwan Hamdani; Muhardi Muhardi; Syawal Satibi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Generally, coal are used for fuel by industry factory at Indonesia. Coal burning produce two of kind waste, that is fly ash and bottom ash. Utilization of coal waste is not optimal yet at this time. This research aims to find out optimum percentage from fly ash and bottom ash mixed by mechanical strength and to know curing effect for 0 and 28 days. The result of proctor standard is increasing proportion bottom ash content on fly ash and bottom ash mixed, then increased dry density maximum while optimum moisture content is decreased. CBR value is increased with increasing bottom ash content. From UCS test, value shear strength (cu) is decreased because increasing bottom ash content. Value from CBR, UCS and Triaxial test is increased after curing for 28 days.Keywords: coal, fly ash, bottom ash, mixed, mechanic characteristic